PENDAMPINGAN DAN ORIENTASI PERLINDUNGAN HARTA ANAK YATIM OLEH WALI DI MAJLIS TA’LIM AL-BIDAYAH, CIANJUR - Ahmad Zain Sarnoto; Windy Dian Sari; Siti Fatimah (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Islamic law instructs the guardians of orphans not to arbitrarily affect the orphans and their property. Because children are part of the younger generation as one of the human resources who have a strategic role in forming a better family. Guardians should not behave unjustly towards orphans